Language and Cultural Motivation of Mazowsze’s Funerals Chrematonims - Sikora, Ewa (Respectus Philologicus, 2016)
The aim of the article is the analysis of semantic names of the funeral homes coming from province of Mazowsze. Onomastic material includes 88 names taken from the Internet Directory “Panorama Firm”. Analysed names of the funeral home were classified into 7 main groups of meaning. Out of them the most popular are the names arising from anthroponyms in which the name of the company owner is dominant. Also the names of the funeral homes taken from Greek, Roman and Egyptian mythology are extremely popular. Similar in quantity are the names emanating from biblical terminology, which refer to characters and places from the Bible. Less numerous are the names in English, with a strong connotation to death, salvation, or referring to the attributes of the funeral. The poorest group of names are those created from the names of the plants. A look into the names collected a variety of emotions, including: pain, loneliness, nostalgia. The motivation for naming the funeral companies is manifold. The main aim is to apply the right gimmick in the form of a name that will attract attention.